STUDY OF CLOTHING QUALITY CONTROL AND ANALYSIS - Nazarova, Matluba; Musayeva, Gulshanoy; Mirzaraximova, Sayyora (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This research study studies the processes of quality control and analysis of clothing products. The work provides information on the quality indicators of clothing products, their assessment criteria, control methods, and modern analysis methods. Also, factors affecting quality at the production stage and in the finished product are analyzed, and ways to identify and eliminate them are considered. The study used laboratory tests, visual inspection, quality assessment methods based on consumer requirements and international standards. As a result of the work, recommendations were developed for improving the clothing quality monitoring system.